Answer :

Formula: –








Given: –


y = xn(acos(logx) + bsin(logx))


y = axncos(logx) + bxnsin(logx)







= xn (na + b)[(n – 1) cos(logx) – sin (logx) ] + (bn – a) xn [(n – 1) sin(logx) + cos(logx)] + (1 – 2n)xn – 1cos(logx)(na + b) + (1 – 2n)xn – 1sin(logx)(bn – a) + a(1 + n2)xncos(logx) + bxn(1 + n2)sin(logx)



Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If y = 3 cos(log Mathematics - Board Papers

If x = t2</sMathematics - Exemplar

If x = a cos θ + Mathematics - Board Papers

If <iMathematics - Exemplar

If y =(tan–1Mathematics - Board Papers

If y = (tan Mathematics - Board Papers

Differentiate <spMathematics - Board Papers

Find<span lang="EMathematics - Board Papers

If y = xx</sMathematics - Board Papers

If x = a cos θ + Mathematics - Board Papers